2010
DOI: 10.2528/pierl09102902
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Coupling Reduction Using Dumbbell Defected Ground Structure for Multiband Microstrip Antenna Array

Abstract: Abstract-A novel design of multiband microstrip antenna array with dumbbell shape defected ground structure (DGS) is presented. The DGS is inserted into the ground plane between the two elements of the antenna array in order to suppress mutual coupling. Both simulation and measurement results verified that the DGS improved the radiation properties of the antenna array. Measurement results of the DGS antenna showed mutual coupling reduction of maximum 5 dB and gain enhancement to 3 dB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 9 publications
0
30
0
Order By: Relevance
“…Due to enhancement of gain in design 2 using DGS structure this antenna will significantly suppress potential interference in existing systems i.e. WLAN applications, X-band [Zulkifli (2010) …”
Section: Discussionmentioning
confidence: 99%
“…Due to enhancement of gain in design 2 using DGS structure this antenna will significantly suppress potential interference in existing systems i.e. WLAN applications, X-band [Zulkifli (2010) …”
Section: Discussionmentioning
confidence: 99%
“…(1,2) where f o is the attenuation pole location, f c is the 3-dB cutoff frequency, Z o is the characteristic impedance and g 1 is given by the prototype value of the Butterworth-type low pass filter. It is found that the values of the equivalent lumped element circuit model are 0.3397 pF, 9.86 nH respectively.…”
Section: Parameters Extractionmentioning
confidence: 99%
“…For these applications, microstrip antennas are preferred because of their advantages such as low profile, light weight and easy design with multi frequency bands. However, a common disadvantage of microstrip antennas is surface wave, which is excited whenever the substrate has dielectric permittivity greater than one [1]. To suppress surface waves, several studies are conducted including defected ground structure (DGS).…”
Section: Introductionmentioning
confidence: 99%
“…Recently several techniques have been introduced for the design of multiband antennas. These include the use of multi-resonators [5], co-planar waveguides [6], defected microstrip structure [7], defected ground structure [8], coupling mechanism [9], reactive loads [10], fractalization [11], genetic optimization [12] and creation of slots [13][14][15].…”
Section: Introductionmentioning
confidence: 99%